Policy Measures to Revive the MSME Sector from the COVID-19 Crises - S, Subramanian (Digital Repository of Theses - SSBM Geneva, 2025)
This research explores the effect of COVID-19 pandemic on Micro, Small, and Medium Enterprises (MSMEs) in India, focusing on their resilience, adaptation to COVID-19, government relief measures, and workforce management. Adopting an exploratory and descriptive research design, data collection has been made using both quantitative and qualitative approaches. Surveys and structured interviews are used to collect data from MSME owners to provide a comprehensive perspective of impact and related policy measures for COVID-19 on MSMEs in India. 143 distributed questionnaires and Likert-scale surveys were collected. After validation, 100 responses were chosen for analysis. The sample comprises 100 MSMEs from the Peenya Industrial Zone, divided into three categories: 6 medium enterprises, 17 small enterprises, and 77 micro enterprises. Surveys were conducted with MSME owners from various sectors and the data collected underwent statistical analysis. Descriptive statistics, which included percentage analysis, summarized the data, while inferential statistics, such as the t-test and F-test (One-Way ANOVA), were used to identify differences in perceptions among various groups. Scheffe's test was conducted for post hoc analysis of paired mean differences. The results indicate that MSMEs were significantly impacted by financial strain because of decreased demand, supply chain disruptions, and operational challenges during the pandemic. Some government relief measures were helpful, but many respondents felt that the policies were inadequate or difficult to access. MSMEs with prior digital infrastructure were more successful in adapting to the crisis, but many faced challenges in pivoting their business strategies or adopting technological innovations. Workforce management, including layoffs and remote working difficulties, was a major concern for MSMEs during the lockdown. In conclusion, the study points out some of the major barriers to MSME recovery, including limited government support, workforce management issues, and slow technological adaptation. The results suggest the need for more targeted policies, better access to resources, and greater investment in digital infrastructure to enhance the long-term resilience of MSMEs in India. Keywords: COVID-19, Impact, Policy, MSME, Resilience, Government Relief Measures